The pharmacist's work in the prevention and care of cervical cancer (Research, Society and Development, 2022)
Cervical cancer is caused by a persistent infection with some types of Human Papillomavirus (HPV). Knowing that the lack of information about this disease and prophylactic and control measures are a set of obstacles to face myths and taboos in the current situation of cancer in Brazil and in the world. The purpose of this article is to evaluate pharmaceutical care in the prevention and care of cervical cancer. A narrative literature review was carried out, based on articles, books, journals and dissertations, available on virtual database sites, published between 2012 and 2022, to analyze the role of the pharmacy professional in the prevention of breast cancer. cervix. This is a qualitative and descriptive study. It was found that the pharmacist is important in prevention, in informing about the need to use condoms (male or female condoms) that prevent infection by HPV through contact with the skin and mucosa of the vulva, perineal region (region between the thighs and ), perianal (region around the anus) and scrotum. It was concluded that the pharmacist still advises that HPV has a high affinity for mucous membranes, and can affect the oral mucosa, in case of oral sex, and also analyzes all possible health problems of the patient and all medications used, in a holistic way, in which it is related to patient care as a whole, without fragmenting it.